Health risk behavior pattern among students from Cartagena, Colombia: prevalence and associated variables - Zuleima Cogollo; Edna Margarita Gomez-Bustamante (SciELO, 2013)
The aim of the study was to determine the prevalence and variables associated with the pattern of risky health behavior (PRHB) among adolescent students in Cartagena, Colombia. A cross-sectional study was designed to investigate PRHB in a random cluster sample of students from middle and high schools. The associations were adjusted by logistic regression. A total of 2,625 students participated in this research, with ages from 10 to 20 years, mean=13.8 years (SD=2.0), and 54.3% were women. A total of 332 students reported PRHB (12.7%, 95%CI 11.4-14.0). Age over 15 years (OR=2.19, 95%CI 1.72-2.79), not being heterosexual (OR=1.98, 95%CI 1.36-2.87), poor/mediocre academic performance (OR=1.87, 95%CI 1.47-2.38), family dysfunction (OR=1.78, 95%CI 1.40-2.28) and male gender (OR=1.58, 95%CI 1.24-2.01) were associated with PRHB. One in every eight students presented a PRHB. It is important to pay greater attention to students who are over 15 years of age, male, not heterosexual, with a poor/mediocre academic performance and a dysfunctional family.